2020
DOI: 10.1111/pbi.13516
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association coupled gene to gene interaction studies unveil novel epistatic targets among major effect loci impacting rice grain chalkiness

Abstract: Rice varieties whose quality is graded as excellent have a lower percent grain chalkiness (PGC) of two per cent and below with higher whole grain yields upon milling, leading to higher economic returns for farmers. We have conducted a genome-wide association study (GWAS) using a combined population panel of indica and japonica rice varieties, and identified a total of 746 single nucleotide polymorphisms (SNPs) that were strongly associated with the chalk phenotype, covered 78 Quantitative Trait Loci (QTL) regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 52 publications
2
43
0
Order By: Relevance
“…RS, a valuable trait was found to have a significant positive correlation with amylose content and was negatively correlated with glycemic index as suggested by several previous reports and thus a suitable parameter for rice consumption to improve the health status of those who are suffering from diabetics, colon cancer, and obesity 7 . We identified nine strong MTAs for RS with significant PVE on chromosomes 1, 2, 6, 8 and 11 (Table 1 ).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…RS, a valuable trait was found to have a significant positive correlation with amylose content and was negatively correlated with glycemic index as suggested by several previous reports and thus a suitable parameter for rice consumption to improve the health status of those who are suffering from diabetics, colon cancer, and obesity 7 . We identified nine strong MTAs for RS with significant PVE on chromosomes 1, 2, 6, 8 and 11 (Table 1 ).…”
Section: Discussionmentioning
confidence: 56%
“…It is the starch portion resistant to enzyme hydrolysis that escapes the small intestine and enters the large intestine where it gets fermented and slowly releases glucose to the bloodstream. Generally, it has been reported that increased level of RS content in rice grains lowers the GI value ensuring a negative correlation with amylose content 7 . Recently low-to-intermediate RS phenotypic variations in rice panel were identified, resulting novel RS associations to numerous genes associated with amylopectin biosynthesis and degradation 7 .…”
Section: Introductionmentioning
confidence: 99%
“…It was found that grain width had a negative pleiotropic effect on grain chalkiness (Zhao et al 2015). However, grain chalkiness was weakly positively correlated with phenotypic variation of grain width, and the key genes affecting grain width were not the cause of chalkiness (Misra et al 2020). It was also found that although several fine-mapped target genes and GWAS loci have been found to influence chalkiness, many have either low or moderate effect (Gong et al 2017;Wang et al 2017;Quero et al 2018;Misra et al 2019).…”
Section: Relationship Of Grain Chalkiness and Grain Shapementioning
confidence: 99%
“…Many QTLs for chalkiness were detected on chromosomes 5, 6 and 8 in different populations and environments (He et al 1999;Tan et al 2000;Wan et al 2005;Hao et al 2009;Liu et al 2011;Chen et al 2011;Guo et al 2011;Liu et al 2012;Li et al 2014;Peng et al 2014;Zhao et al 2015;Chen et al 2016;Gao et al 2016;Yun et al 2016;Zhao et al 2016;Wang et al 2017;Zhu et al 2018a;Misra et al 2019;Misra et al 2020). On chromosome 8, the hotspot region of the QTLs for chalkiness was located on the long arm (Li et al 2003;Wan et al 2005;Hao et al 2009;Guo et al 2011;Liu et al 2012;Gao et al 2016;Zhao et al 2016;Wang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation